The Electric Field Guided HaCaT Cell Migration Through the EGFR/p38 MAPK/Akt Pathway - Huajian Zhou; Shihao Zhang; Xiaoli Jin; Chunxian A; Peng Gong; Sanjun Zhao (Current Issues in Molecular Biology)
Previous studies have shown that the endogenous electric field (EF) is an overriding cure in guiding cell migration toward the wound center to promote wound healing, but the mechanism underlying is unclear. In this study, we investigated the molecular mechanism of electric field-guided cell migration in human keratinocyte HaCaT cells. Our results showed that HaCaT cells migrate toward the anode under EFs. The phosphorylation levels of p38 MAPK and Akt were obviously elevated in the EF. Knocking down p38 MAPK obviously abolished directed migration of HaCaT cells under the EFs. Inhibiting p38 MAPK by SB203580 impaired the EF-guided cell migration. The electric field may guide HaCaT cell migration through the EGFR/p38 MAPK/Akt pathway.